Carl Jung and Edmond Cros: the Spirit of the Times and the Cultural Subject (2017)
This paper examines the relation between the concept of “spirit of the times” used by Carl G. Jung in his approach to art and science, enriched by his concept of “collective unconscious”, and the notion of “cultural subject” proposed by Edmond Cros. Even though these concepts emerge in different historical moments, both Cros and Jung approach how culture and the symbolic –what is given- are reproduced in every social and artistic production –what is created-. This article examines the developments made by the Swiss psychoanalyst in reference to the creative process and the literary phenomenon, in order to establish a comparison between the postulates of both thinkers.